Phosphodiesterases PDE2A and PDE10A both change mRNA expression in the human brain with age, but only PDE2A changes in a region-specific manner with psychiatric disease - Farmer, Reagan (Cell Signal, 2020)
Many studies implicate altered cyclic nucleotide signaling in the pathophysiology of major depressive disorder (MDD), bipolar disorder (BPD), and schizophrenia (SCZ). As such, we explored how phosphodiesterases 2A (PDE2A) and 10A (PDE10A)—enzymes that break down cyclic nucleotides—may be altered in brains of these patients. Using autoradiographic in situ hybridization on postmortem brain tissue from the Stanley Foundation Neuropathology Consortium, we measured expression of PDE2 and PDE10 mRNA in multiple brain regions implicated in psychiatric pathophysiology, including cingulate cortex, orbital frontal cortex (OFC), superior temporal gyrus, hippocampus, parahippocampal cortex, amygdala, and the striatum. We also assessed how PDE2A and PDE10A expression changes in these brain regions across development using the Allen Institute for Brain Science Brainspan database. Compared to controls, patients with SCZ, MDD and BPD all showed reduced PDE2A mRNA in the amygdala. In contrast, PDE2A expression changes in frontal cortical regions were only significant in patients with SCZ, while those in caudal entorhinal cortex, hippocampus, and the striatum were most pronounced in patients with BPD. PDE10A expression was only detected in striatum and did not differ by disease group; however, all groups showed significantly less PDE10A mRNA expression in ventral versus dorsal striatum. Across development, PDE2A mRNA increased in these brain regions; whereas, PDE10A mRNA expression decreased in all regions except striatum. Thus, PDE2A mRNA expression changes in both a disorder- and brain region-specific manner, potentially implicating PDE2A as a novel diagnostic and/or patient-selection biomarker or therapeutic target.